A semi-rigid tricarboxylate ligand based Co(ii) coordination polymer: construction and applications in multiple sensing. (13th February 2020) - Li, Bai-Ling; Wang, Jun-Ku; Gao, Jin-Sheng; Yu, Ying-Hui; Ma, Dong-Sheng
Abstract : A cobalt coordination polymer was prepared, which expresses multiple fluorescence responses to transition metal ions, antibiotics, pesticides and nitrobenzene. Abstract : A two-dimensional (2D) coordination polymer [Co2 (OH)(H2 O)2 (cbca)·2H2 O] n (CP 1 ) (H3 cbca: 4′-(1-carboxyethoxy)-[1, 1′-biphenyl]-3, 5-dicarboxylic acid) with a topological (3, 6) connection point structure was synthesized by a hydrothermal method. Single-crystal X-ray analysis revealed that the 2D structure is comprised of tetranuclear cobalt clusters and semi-rigid cbca ligands connected through strong Co–O bonds. It has been found that CP 1 can be used as an effective multiple fluorescent sensor for detecting iron ions, specific nitro compounds, antibiotics and pesticides. Further investigations show that the fluorescence quenching originates from different mechanisms. Among them, the redshift phenomenon generated during the detection of some analytes can also effectively distinguish analytes, which is rarely mentioned in previous studies.